Strategi Kepala Madrasah dalam Mewujudkan Pendidikan yang Berkualitas di Mts Nurul Iman Izzati - Ok Reza Fathurrahman; Salsabila Yasmin; Denny Fitriani; Marhatul Fatwa; Putri Rahayu (Prodi Perpustakaan dan Sains Informasi, 2023)
Varioius knoiwleidgei and skills arei reiquireid in thei foirmulatioin oif an eiffeictivei supeirvisioin plan oir strateigy. Theireifoirei, thei right strateigy is neieideid froim thei heiad oif thei madrasa in supeirvising soi that quality eiducatioin can bei reializeid. Thei purpoisei oif this study was toi deiteirminei thei supeirvisioin proigram strateigy, thei impleimeintatioin oif thei supeirvisioin proigram and thei eivaluatioin oif thei madrasa principal supeirvisioin proigram. This study useid a deiscriptivei meithoid with a qualitativei approiach. Data coilleictioin teichniqueis throiugh: oibseirvatioin, inteirvieiws, and doicumeintatioin. This reiseiarch was coinducteid at MTs Nurul Iman Izzati. Thei reiseiarch subjeict was thei heiad oif thei madrasa. Thei reisults shoiweid that: (1) acadeimic supeirvisioin was carrieid oiut baseid oin thei visioin, missioin and oibjeictiveis oif thei madrasa toi improivei quality eiducatioin (2) In foirmulating schoioil proigrams, teiacheirs weirei givein thei oippoirtunity toi proividei input and eivaluatei thei proigrams coimpileid (3 ) Thei strateigy oif supeirvising thei heiad oif thei madrasa by visiting, coilleicting daily teiacheir joiurnals and oibseirvatioins. (4) Thei Madrasah Heiad eivaluateis thei supeirvisioin proigram by loioiking at studeint gradeis, bringing thei reisults oif thei supeirvisioin asseissmeint toi thei Madrasa Supeirinteindeint froim thei Ministry oif Reiligioin, and discussing deificieincieis that oiccur in thei teiaching and leiarning proiceiss toi curriculum reipreiseintativeis.